Analysis of Figurative Language in Selena Gomez’s Album Rare - Putri Wirastuti, I Gusti Agung; Yuliastuti, Ni Putu (Journal on Studies in English Language Teaching (JOSELT), 2024)
Analysis of the types and meanings of metaphorical language in Selena Gomez's song lyrics from the album Rare is the goal of this study. Figurative language, or the manner an author describes what will be delivered, is a style of language use in essays. The use of language in certain circumstances, by specific writers, and for specific subjects is discussed in style (linguistic style).(Putra & Puspitasari, 2020). The researcher analyzing five song lyrics on Selena's "Rare" album, namely the songs Vulnerable, Bad Liar, Lose You to Love Me, Ring, and People you know. The researcher analyses figurative language expressions, namely hyperbole, simile, and repetition. After the analysis, researcher found 15 data that repetition expressions get the highest frequency, which is 6 expressions. And followed by hyperbole expressions which get 5 expressions. The lowest frequency expression is simile which get 4 data. This fact shows that figurative language is important in song lyrics. Expressions of figurative language influence song lyrics to make them more beautiful and interesting and able to insert hidden messages for listeners.